Isotopic lifting of Newtonian mechanics - Santilli, Ruggero Maria (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
We present a simple isotopic generalization of the ordinary differential calculus, here called isodifferential calculus, which is based on an axiom-preserving generalization of the unit with compatible generalizations of fields, vector spaces and manifolds. The new calculus is applied to the isotopic of using of Newton's equations of motion. We show that the isotopic equations possess capabilities which are absent for the conventional equations, such as: the representation of the actual nonspherical and deformable shape of particles; the admission of nonlocal-integral forces; and the representation of onnpotential (variationally non-self-adjoint)interactions via the unit of the theory.